PENGARUH AUDIT KINERJA DAN PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PUBLIK PDAM KOTA BAUBAU - Said Saleh Salihi (Jurnal Manajemen dan Kewirausahaan, 2022)
This study aims to analyze the effect of performance audit and internal control on public accountability at the Regional Public Company for Drinking Water in Baubau City. The population in this study were all permanent employees totaling 112 people. The sampling technique used the Slovin formula so that the total sample was 32 people. This study uses multiple regression analysis obtained the equation Y = 1.445 + 0.403 X1 + 0.257 X2. The correlation value (R) of 0.805 means that there is a very strong correlation between performance audit and internal control on public accountability. While the coefficient of determination test of 0.648 (64.8%) means that the contribution of performance audit and internal control affects public accountability by 64.8%. The results of the t test show that performance audit has a significant effect on public accountability and internal control has no significant effect on public accountability with a significant value of 0.041 less than 0.05 and 0.256 greater than 0.005. The results of the F test show that the performance audit and internal control together have a significant effect on public accountability with a significant F value of 0.000 which is smaller than 0.05. This shows that the proposed hypothesis can be accepted.